PENERAPAN KAWAL DESA UNTUK KEBUTUHAN TATA KELOLA DESA SIRNAGALIH BAYONGBONG - Mulyani, Asri; Juliansyah, Fauzan Romi; Febrianti, Tiara; Rengganis, Nadia Fauziah; Saparudin, Hopid; Slamet, Bagus; Latif, A. Abdul; Haolilah, Siti; Fathon, Ahmad; Wahdaniah, Hamidah Nur; Ramdani, Idham; Putri, Elsinta Ismawati; Jamiludin, Irfan; Rahayu, Maulida Fasha; Saadah, Roro; Alfiansyah, Dandan; Ahzam, Faiq Muhammad; Alhakim, Much Kahfi; Nurpajar, Dini Siti; Gustiawan, Restu Fajar (Jurnal PkM MIFTEK, 2023)
Along with current developments in technology and information, it is hoped that villages can implement applications that can help administration and facilitate communication with the community. Kawal Desa is an application or platform used for village governance needs and interaction between residents and officials. Based on these problems, the aim of this Work Lecture activity is to implement the Kawal Desa application to help village officials and the community manage community activities more effectively and efficiently. The approach used is by providing assistance and training to village officials and community leaders. As a result of implementing village guard, village administration can be well organized, and make it easier to monitor community activities and communication.